Thermal properties of acylated low molecular weight chitosans - Tiew, Shu Xian; Misran, Misni (Chemical Society of Pakistan, 2019)
Summary: Acylated low molecular weight chitosans (LChA) were prepared from nucleophilic acylation of chitosan using acid anhydrides of short and medium chain length (4 - 10) to study the response of applied heat as a function of acyl chain length. Thermogravimetric analysis (TGA) revealed the decomposition of LChA consisted of glucosamine and acyl-glucosamine units around 141 - 151°C to 400 - 410°C. Both TGA and differential scanning calorimetry (DSC) analyses indicated that the introduction of acyl groups disrupted the hydrogen bonding of chitosan, the effect was more prominent as the degree of substitution and chain length of LChA increased. Grafting of acyl chains lowered the kinematic viscosity of LChA as the disruption of hydrogen bonding led to decreased hydrodynamic volume. Field emission scanning electron micrographs showed that LChA with longer chains having larger particle size due to bigger occupancy volume of acyl chains during spray drying. © 2019 Chemical Society of Pakistan. All rights reserved.